Analyzing causes of the death of Ferns (Pteridophyta) in the Padang Savana, Taman Nasional Bromo Tengger Semeru (TN-BTS) - Eko Purnomo; Nilana Izzati; Robbi Mauizzatul Hikmah; Diyana Sabila Rusydina; Lathifah Nurul Fauzi; Ibnu Sina Rafiq Romawan (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
The Padang Savana area of Bromo Tengger Semeru National Park (TN-BTS) is located at an altitude of 750-3676 m above sea level so that it has a high biodiversity with a distinctive vegetation character. Ferns (Pteridophyta) is one of the vegetation that dominates about 35% of the Bromo Conservation Area. The ferns in the location show a dry and dead physical condition. This study aims to analyze the causes of death of ferns (Pteridophyta) in the Padang Savana Bromo Tengger Semeru National Park. The research method used is a qualitative descriptive method and the data obtained from direct observation to the savanna of Bromo Tengger Semeru National Park (TN-BTS) and face-to-face interviews without guidance to resource persons. The sampling location is at an altitude of 2026 masl, temperature 24.4°C, air pressure 792.5 HPA, with the object of research in the form of a sprig of ferns (Pteridophyta) complete with dead leaf roots and is considered to represent all ferns (Pteridophyta) in the savanna. The data obtained from the resource persons were then analyzed using literature studies. The results showed that the death of ferns (Pteridophyta) was caused by several factors such as the presence of allelopathic substances produced from Imperata cylindrica, soil texture, and eruption disasters. Thus, the surrounding environment is very influential on the life of ferns (Pteridophyta) The results showed that the death of ferns (Pteridophyta) was caused by several factors such as the presence of allelopathic substances produced from Imperata cylindrica, soil texture, and eruption disasters. Thus, the surrounding environment is very influential on the life of ferns (Pteridophyta) The results showed that the death of ferns (Pteridophyta) was caused by several factors such as the presence of allelopathic substances produced from Imperata cylindrica, soil texture, and eruption disasters. Thus, the surrounding environment is very influential on the life of ferns (Pteridophyta). ©2021 JNSMR UIN Walisongo. All rights reserved.